Incidence and prevalence of hepatitis B in patients with diabetes mellitus in the UK: A population‐based cohort study using the UK Clinical Practice Research Datalink. Issue 5 (17th January 2018) - Ferreira, G. L. C.; Marano, C.; De Moerlooze, L.; Guignard, A.; Feng, Y.; El Hahi, Y.; van Staa, T.
Summary: We assessed the incidence and prevalence of hepatitis B (Hep B) in patients with or without diabetes mellitus (DM) using the UK Clinical Practice Research Datalink (CPRD). This was a retrospective, observational study of diabetic and nondiabetic cohorts aged 0‐80 years using CPRD (NCT02324218). Incidence rates (IR) for each cohort were calculated. Crude and adjusted (Poisson regression) IR ratios (IRR) were estimated with 95% confidence intervals (CI) to compare the cohorts. Hep B prevalence stratified by age, and hospitalization related to Hep B was also calculated. Of 7 712 043 subjects identified, 4 839 770 were included (DM: 160 760; non‐DM: 4 679 010). Mean ages were 54.4 and 32.0 years, and 57.20% and 50.14% were male in the diabetic and nondiabetic cohorts, respectively. Hep B was identified in 29 diabetic and 845 nondiabetic subjects; IR was 4.03 per 100 000 person‐years and 2.88 per 100 000 person‐years, respectively. The adjusted IRR was 1.00 (95% CI: 0.70‐1.50) between diabetic and nondiabetic cohorts. Hep B prevalence was higher in the diabetic cohort (0.01%‐0.26%) than in the nondiabetic cohort (0.00%‐0.03%) across the different age groups. Hep B‐associated hospitalization IR was higher in the diabetic cohort (4.98‐10.91) than the nondiabetic cohort (0.26‐2.44). The Hep B IR, hospitalization and prevalence were higher in males in both cohorts. In conclusion, the risk of incident Hep B diagnosis in the diabetic cohort was not different from that in the nondiabetic cohort. However, prevalence of Hep B and Hep B‐associated hospitalization rate was higher in the diabetic than in the nondiabetic cohort.